The Management Living Values Education Program in Improving The Character of Religious Moderation in Achsaniyah Islamic Boarding School Kudus - Elya Umi Hanik; Abu Choir; Husni Mubarok (Lembaga Pendidikan Hikmatun Najah Blora, 2023)
The aim of this study is to explain the Management of the Living Values Education Program in Improving the Character of Religious Moderation in Achsaniyah Islamic Boarding School. This research is a qualitative research using interviews, observation and documentation in collecting data.Â The collected data were analyzed through a data reduction process by selecting data related to the research objectives. This research concludes that for teachers can develop universal values, namely cooperation, freedom, happiness, honesty, humility, love, peace, respect, responsibility, simplicity, tolerance, and unity so that if these values have been internalized in the teacher. The teacher will transfer and instill these values in students' habits and make living values a part of their lives. The value-based activities in the Living Values Education Program are designed to motivate students, in this case the Santri, to invite them to think about themselves, others, the world, and values in an interrelated way. This activity aims to strengthen and to provoke the potential, creativity and talents of each student which in the process will develop personal, social and emotional skills, in line with social skills that are peaceful and full of cooperation with others. The indicators of religious moderation that will four things are used, namely: 1) national commitment; 2) tolerance; 3) non-violence and 4) accommodating to local culture. The character of religious moderation in the Achsaniyah Islamic boarding school was reflected in the attitude of the accompanying teacher of the Santri and the attitude of the santi with character. The contribution of this research provides information that the existence of a living value management program at the Achasniyah Islamic boarding school can foster the religious character of the students so that it can become a reference for development at other institutions and also for further research.